2016
DOI: 10.1007/s00442-016-3573-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light and nutrients on periphyton and the fatty acid composition and somatic growth of invertebrate grazers in subtropical streams

Abstract: Algal polyunsaturated fatty acids (PUFA), essential for somatic growth and reproduction of aquatic animals, are influenced by ambient environmental conditions, including light and nutrients. Few studies have addressed the extent to which changes in algal PUFA can influence stream herbivore PUFA profiles and the implications for stream food webs. We manipulated subtropical stream periphyton by applying two light levels (open and shaded canopy) and two nutrient regimes (ambient and enriched) to investigate the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
76
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(85 citation statements)
references
References 47 publications
4
76
0
Order By: Relevance
“…Our results suggest that the periphyton FA effect on the FA composition of macroinvertebrate grazers may lead to different feeding strategies for EPA requirements across seasons, and the periphyton effect was stronger than the effect of grazer species identity. The seasonal increase in periphyton EPA% was reflected in the FA composition of grazer tissues, consistent with previous studies (Torres‐Ruiz et al ; Guo et al a ). The observed correlations between grazer EPA and periphyton EPA could represent a combination of spatiotemporal variability in resources and a physiological need to fulfill EPA requirements in these grazers.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results suggest that the periphyton FA effect on the FA composition of macroinvertebrate grazers may lead to different feeding strategies for EPA requirements across seasons, and the periphyton effect was stronger than the effect of grazer species identity. The seasonal increase in periphyton EPA% was reflected in the FA composition of grazer tissues, consistent with previous studies (Torres‐Ruiz et al ; Guo et al a ). The observed correlations between grazer EPA and periphyton EPA could represent a combination of spatiotemporal variability in resources and a physiological need to fulfill EPA requirements in these grazers.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the response variables were individual FA% (e.g., EPA, ARA, DHA, ALA, and LIN, respectively), with consumers and dietary resources (invertebrate FFG, periphyton, fresh leaves, and submerged leaves) as the fixed factors and sites and seasons as the random factors. The protocol for linear mixed‐effect model fit and validation followed Zuur et al () and Guo et al ( a ). Restricted maximum likelihood estimation was used to fit models, and the likelihood ratio test was used to compare and select fitted models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings might be related to physiological responses of periphyton to differences in nutrient concentrations. Some studies have reported that added nutrients lead to an increase in the proportions of ALA in periphyton (Cashman, Wehr, & Truhn, 2013;Guo et al, 2016;Hill et al, 2011), but unfortunately we did not analyse periphyton fatty acids in this study. In phytoplankton, low nutrient concentrations lead to the production of PUFA-poor triacylglycerols, whereas high nutrient concentrations lead to an increase of PUFA-rich galactolipids in the algae (Guschina & Harwood, 2009).…”
Section: Discussionmentioning
confidence: 91%
“…Consumers receive most of the PUFAs they need, directly or indirectly, from photosynthetic primary producers (Bell & Tocher, 2009) and the fatty acid composition of primary consumers usually reflects that of primary producers (Guo, Kainz, Sheldon, & Bunn, 2016;Torres-Ruiz, Wehr, & Perrone, 2007). Higher-level consumers in the food web may then obtain PUFAs via feeding on lower trophic levels that serve as integrators of the high-quality food (Strandberg et al, 2015;Twining, Brenna, Hairston, & Flecker, 2016).…”
Section: Introductionmentioning
confidence: 99%